Acting the part: Emotional intelligence and job satisfaction as predictors of emotional labor in travel agencies. (April 2021) - Knežević, Milena Nedeljković; Petrović, Marko D; Kovačić, Sanja; Mijatov, Maja; Vuković, Darko B; Kennell, James
Employees of retail travel agencies in sales roles can have long-lasting, direct contact with tourists which, in the case of poor customer service, can be extremely problematic for businesses. Because of this, it is important to understand how employees manage their emotions to help them to remain satisfied with their work, thus contributing to the satisfaction of tourists. However, job satisfaction, emotional intelligence and emotional labor in tourism have not previously been studied together as variables in a single model. This research analyses the mediating role of emotional intelligence in the relationship between job satisfaction and emotional labor in travel agencies, as well as job satisfaction as an antecedent of emotional labor. Data were collected from 160 employees of 45 travel agencies in the Serbian cities of Belgrade and Novi Sad. Results show that employees' emotional intelligence mediates the positive relationship between job satisfaction and emotional labor. Management implications: Increasing employees' emotional intelligence through training and development and actively recruiting employees with high emotional intelligence will reduce emotional exhaustion and improve customer satisfaction for retail travel agencies. Future research should include employees from other countries, in order to make comparisons and to validate results, as well as to test the created model by structural equation modelling (SEM), involving some other possible mediators, such as socio-demographics, personality traits or work motivation.